Multivisceral surgery in a giant dedifferentiated retroperitoneal liposarcoma: a case report - Cruz-León, Cristhian Hernán (2024)
Liposarcomas are malignant neoplasms of mesodermal origin derived from adipose tissue that form part of 10-15% of soft tissue sarcomas. For its diagnosis, the presence of a palpable abdominal mass and imaging studies such as: CT, MRI and PET are taken into account, which allow defining the appearance, size, location and organic relationships of the tumor. The case of a 51-year-old woman with a mass of fatty content and soft tissues in the retroperitoneal region is reported, in whose CT scan measures 25.8 cm x 23.5 cm x 13.5 cm, which invades and displaces the left kidney superiorly. the abdominal aorta to the right, in addition to the left ureter, the adrenal gland and which moves the descending colon forward. She underwent retroperitoneal tumor resection with multivisceral surgery that included left nephroureterectomy and left colectomy plus side-to-end colorectal anastomosis. The histopathological report of the surgical specimen corresponds to a high-grade dedifferentiated liposarcoma weighing 6,776 kg, measuring 42 x 30 x 12 cm.